Tissue thickness estimation for high precision head-tracking using a galvanometric laser scanner - A case study - Wissel, Tobias; Stuber, Patrick; Wagner, Benjamin; Durichen, Robert; Bruder, Ralf; Schweikard, Achim; Ernst, Floris (2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society, 2014)
Marker-less optical head-tracking constitutes a comfortable alternative with no exposure to radiation for realtime monitoring in radiation therapy. Supporting information such as tissue thickness has the potential to improve spatial tracking accuracy. Here we study how accurate tissue thickness can be estimated from the near-infrared (NIR) backscatter obtained from laser scans. In a case study, optical data was recorded with a galvanometric laser scanner from three subjects. A tissue ground truth from MRI was robustly matched via customized bite blocks. We show that Gaussian Processes accurately model the relationship between NIR features and tissue thickness. They were able to predict the tissue thickness with less than 0.5 mm root mean square error. Individual scaling factors for all features and an additional incident angle feature had positive effects on this performance.